Congenital myasthenia syndrome due to CHRNA1 mutation resulting in respiratory failure - Chiramel, Jeslin Joshy; C., Praveen Kumar; Thirumalesh, Parimala V. (International Journal of Contemporary Pediatrics, 2025)
CMS is an inherited disorder, characterized by defective transmission at Neuromuscular Junction affecting from birth or soon after. It results in fatigue and muscle weakness because of genetic abnormalities that interfere with the neuromuscular junction's ability to function. The most typical signs of CMS include eyelid drooping, breathing difficulties, muscle weakness and weariness with variations depending on specific genetic mutations. Clinical examinations, neurophysiologic tests, and genetic analyses are frequently combined to make the diagnosis of CMS. Although there is no known treatment for CMS, many patients may control their symptoms and lead relatively normal lives with the right care. A newborn with CMS due to CHRNA1 gene mutation is described in this article, along with its very early onset. The CHRNA1 mutation is a rare variant in the Indian population. Due to muscle weakness, the neonate in this case developed severe respiratory distress and later succumbed to death despite rigorous life-saving measures.